2008
DOI: 10.1158/1535-7163.mct-08-0450
|View full text |Cite
|
Sign up to set email alerts
|

Keratin down-regulation in vimentin-positive cancer cells is reversible by vimentin RNA interference, which inhibits growth and motility

Abstract: At later stages of tumor progression, epithelial carcinogenesis is associated with transition to a mesenchymal phenotype, which may contribute to the more aggressive properties of cancer cells and may be stimulated by growth factors such as epidermal growth factor and transforming growth factor-B. Previously, we found that cells derived from a nodal metastatic squamous cell carcinoma are highly proliferative and motile in vitro and tumorigenic in vivo. In the current study, we have investigated the role of vim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
79
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 45 publications
10
79
0
6
Order By: Relevance
“…For example, forced expression of keratin 18 in a metastatic breast cancer cell line reduced the vimentin expression level, invasiveness in vitro, and metastatic spread in mice (18). In a similar way, stable silencing of vimentin in squamous carcinoma cells resulted in re-emergence of keratins and a concomitant reduction in cell invasiveness and tumorigenic potential (57). Conversely, suppression of both K8/18 in non-small cell lung cancer cell lines increased their invasiveness (58).…”
Section: Discussionmentioning
confidence: 95%
“…For example, forced expression of keratin 18 in a metastatic breast cancer cell line reduced the vimentin expression level, invasiveness in vitro, and metastatic spread in mice (18). In a similar way, stable silencing of vimentin in squamous carcinoma cells resulted in re-emergence of keratins and a concomitant reduction in cell invasiveness and tumorigenic potential (57). Conversely, suppression of both K8/18 in non-small cell lung cancer cell lines increased their invasiveness (58).…”
Section: Discussionmentioning
confidence: 95%
“…Studies of human epithelial carcinomas, such as breast cancer, hepatocellular carcinoma, colon carcinoma, and prostatic adenocarcinoma, have shown that vimentin expression can be correlated with tumour invasion and a poor prognosis. [8][9][10][11][27][28][29][30][31][32] Several previous publications have detected the expression of vimentin in oral squamous cell carcinoma patients or cell lines. 8,40,50 To our knowledge, this is the first study to show that the overexpression of vimentin in oral squamous cell carcinoma specimens was closely associated with local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…27 Numerous data have shown that vimentin can be expressed in migratory epithelial cells that are involved in embryogenesis and organogenesis, wound healing, or tumour invasion. [28][29][30][31] Gilles et al 29 have shown that the vimentin promoter is a target of the b-catenin/TCF pathway, which suggests that this functional regulation of epithelial cells is involved in invasion and/or migration. 32 Currently, it is thought that the invasive front of tumours is the region containing the most useful prognostic information because, presumably, the most invasive cells are located there.…”
mentioning
confidence: 99%
“…Vim is a component of the cytoskeleton, is involved in cell adhesion and migration, and also regulates apoptosis and signal transduction in tumor tissues (6)(7)(8). EMT, as a target involved in invasion and metastasis mechanisms, has been revealed to result in the poor prognosis of patients with triple negative breast cancer and pancreatic cancer (9,10). EMT may be directly or indirectly mediated by various factors including snail, slug and twist.…”
Section: Introductionmentioning
confidence: 99%